Mechanical behavior of articular cartilage after osteochondral autograft transfer in an ovine model. - Kleemann, R; Schell, H; Thompson, M; Epari, DR; Duda, G; Weiler, A (2007)
BACKGROUND: Grafting of autologous hyaline cartilage and bone for articular cartilage repair is a well-accepted technique. Although encouraging midterm clinical results have been reported, no information on the mechanical competence of the transplanted joint surface is available. HYPOTHESIS: The mechanical competence of osteochondral autografts is maintained after transplantation. STUDY DESIGN: Controlled laboratory study. METHODS: Osteochondral defects were filled with autografts (7.45 mm in diameter) in one femoral condyle in 12 mature sheep. The ipsilateral femoral condyle served as the donor site, and the resulting defect (8.3 mm in diameter) was left empty. The repair response was examined after 3 and 6 months with mechanical and histologic assessment and histomorphometric techniques. RESULTS: Good surface congruity and plug placement was achieved. The Young modulus of the grafted cartilage significantly dropped to 57.5% of healthy tissue after 3 months (P < .05) but then recovered to 82.2% after 6 months. The aggregate and dynamic moduli behaved similarly. The graft edges showed fibrillation and, in some cases (4 of 6), hypercellularity and chondrocyte clustering. Subchondral bone sclerosis was observed in 8 of 12 cases, and the amount of mineralized bone in the graft area increased from 40% to 61%. CONCLUSIONS: The mechanical quality of transplanted cartilage varies considerably over a short period of time, potentially reflecting both degenerative and regenerative processes, while histologically signs of both cartilage and bone degeneration occur. CLINICAL RELEVANCE: Both the mechanically degenerative and restorative processes illustrate the complex progression of regeneration after osteochondral transplantation. The histologic evidence raises doubts as to the long-term durability of the osteochondral repair.